Mechanisms of Aqueous Fluid Infiltration and Redistribution in a Lower‐Crustal Pseudotachylyte‐Bearing Fault - Michalchuk, Stephen Paul; Lueder, Mona; Gies, Nils B.; Ohl, Markus; Hermann, Jörg; Plümper, Oliver; Menegon, Luca (Geochemistry, geophysics, geosystems : G3, 2025)
Coseismic fracturing in the strong, dry, and metastable plagioclase‐rich lower‐crust is an effective mechanism for creating pathways for fluids to infiltrate the host rock, kick‐start metamorphism, and potentially lead to rheological weakening. In this study, we have characterized the damage zone flanking a lower‐crustal pseudotachylyte (solidified frictional melt produced during seismic slip) within an anorthosite to determine the mechanisms of incipient aqueous fluid infiltration and redistribution in a lower‐crustal seismogenic fault. Pulverization‐style fracturing of the host anorthosite resulted in the comminution of the host plagioclase (plagioclase1) grains and the growth of very fine (<20 μm) grained secondary plagioclase neoblasts (plagioclase2) filling the fractures. Fluid‐assisted grain growth accompanied surface‐ and strain‐energy minimization grain growth in the healing and sealing of the fractures. This process was not associated with the densification nor the creation of new reaction‐induced porosity. Fourier transform infrared maps transecting the damage zones show the presence of H2O species along the plagioclase1 and plagioclase2 grain boundary regions, as well as incorporated into plagioclase2 grain interiors. Grain‐size sensitive creep of fine‐grained plagioclase localized along the pseudotachylyte margin where fracturing was most pervasive. In the absence of reaction‐induced porosity, strain localization is determined by repeated occurrences of extreme grain‐size reduction in addition to the mobilization of aqueous fluid to the grain boundary regions, to the extent in which these fine‐grained wet plagioclase2 layers are volumetrically dominant over dry, coarse plagioclase1 fragments. This forms a layer capable of deforming by grain‐size sensitive creep and sustaining the mobility of fluids. Plain Language Summary Earthquakes are effective in fracturing rocks and creating pathways for fluids to flow and infiltrate deep within an otherwise dry and strong host rock. Fluids interacting with these dry and strong rocks, especially those in the lower crust at >25 km depth, may induce chemical reactions, produce new weaker minerals, and deteriorate the overall strength of the host rock. Areas that have become weaker will localize deformation and form ductile shear zones. The mechanistic processes that produce this transformation are poorly constrained and are the subject of this study. Using specialized microscopy techniques that measure the mineral's crystallographic orientation and the H2O content within plagioclase feldspar, we document that a single‐event earthquake rupture in the lower crust can liberate and mobilize a small amount of locally sourced H2O over short distances along fractures. However, without a sustainable source of H2O, fractures will heal themselves and consume the free H2O. We determined that repeated earthquake events, which repeatedly fracture the dry host rock into increasingly smaller fragments and mobilize fluids after each event, will form volumetrically thicker sequences of wet fine‐grained layers that can easily localize strain and form ductile shear zones. Key Points Plagioclase in the damage zone of a lower‐crustal pseudotachylyte deformed via pulverization‐style fragmentation Liberated H2O as a result of the earthquake remained in grain boundary regions and facilitated neoblast growth and healing of fractures Repeated fragmentation and comminution in addition to fluid at the grain boundaries are required to facilitate viscous deformation